Amber pendants from the peucetian necropolis of Santo Stefano at Gravina in Puglia. The case of tomb n. 28 (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This paper analyzes the presence of amber artifacts in the Peucetian necropolis of Strada Santo Stefano in Gravina in Puglia (BA). It has been chosen to focus on one single tomb, number 28, which includes an outstanding pendant with teardrop shape. In the grave were also found some remarkable ornamental objects and vases, some figured, which allow to give a possible interpretation of the burial.
Keywords: Gravina; Strada Santo Stefano; amber; ornamental objetcs; apulian pottery